Creativity, intelectual abilities and response styles: Implications for academic performance in the secondary school - Limiñana Gras, Rosa María; Bordoy, Manuel; Juste Ballesta, Graziella; Corbalán Berna, Javier (Anales de Psicología / Annals of Psychology, 2010)
The aim of this paper is to study the creative competence of a specific sample of secondary pupils in a multicultural and multilingual school context, taking into consideration their intellectual abilities, re-sponse style and academic performance in the different subject areas of the secondary education. The sample consists of 75 pupils at the European School of Alicante– a European Commission funded school– in their 5th year of the secondary school. . The average age is 15 years old with a range between 14 and 17 years old. 56% are male pupils; 44% female pupils. For the evaluation of their creativity, the CREA test (Corbalán, Martínez, Donolo, Alonso, Tejerina y Limiñana, 2003) has been used. This test aims at measuring creative intelligence through an indicator of generation of questions. For the evaluation of the intellectual abilities, the EFAI test (Evaluación Factorial de las Aptitudes Intelectuales; Santamaría, Arribas, Pereña & Seisdedos, 2005) has been used. This test contains different sets of questions referred to the 5 basic abilities (Spatial, Numerical, Reasoning, Verbal and Memory). It also offers measurements related to General Intel-ligence (Ig) and assesses the response style (Speed, Efficiency) and con-tains the subtest of Verbal Fluency of the PMA (Primary Mental Abilities; TEA, 2002; Thurstone & Thurstone, 1989) The academic performance was measured through the marks in core subjects and through the average mark for the 1st semester. The results indicate that there are significant relationships among some intellectual abilities, the academic performance and the creativity, which moreover seem to be modulated by the gender variable. The analysis of the variables according to the creative perform-ance of this sample has allowed us to identify the most significant intellec-tual abilities related to the creative performance and to consider its impli-cations for academic performance in general.